2018
DOI: 10.3892/ijmm.2018.3587
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine promotes chondrocyte proliferation via the Wnt/β‑catenin signaling pathway

Abstract: The present study investigated the mechanism underlying the effects of glucosamine (GlcN) on the proliferation of chondrocytes isolated from the knee cartilage of Sprague-Dawley rats. Chondrocytes were treated with various concentrations of GlcN or without GlcN. The effects of GlcN on chondrocyte proliferation were determined using reverse transcription-polymerase chain reaction, western blot analysis and immunohistochemistry. The results indicated that GlcN significantly improved chondrocyte viability, accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…Indeed, different studies showed the effects of GS in reducing expression of COX-2, PGE2 production, and inhibiting activation of the NF-κB pathway in human OA chondrocytes and synoviocytes [33][34][35]. Furthermore, GS promoted chondrocyte proliferation and proteoglycan production, while it decreased the expression of inducible form of nitric oxide (iNOS), IL-6, and TNF-α and matrix degrading factors [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, different studies showed the effects of GS in reducing expression of COX-2, PGE2 production, and inhibiting activation of the NF-κB pathway in human OA chondrocytes and synoviocytes [33][34][35]. Furthermore, GS promoted chondrocyte proliferation and proteoglycan production, while it decreased the expression of inducible form of nitric oxide (iNOS), IL-6, and TNF-α and matrix degrading factors [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…The WNT/β‐catenin signaling pathway in an activated state has been demonstrated to be responsible for escalated β‐catenin levels in articular cartilage and could further lead to cartilage changes in OA at the early stage . Cumulative studies have documented the association between the activity of the WNT/β‐catenin signaling pathway and chondrocyte proliferation and differentiation .…”
Section: Discussionmentioning
confidence: 99%
“…In the independent process, the β-catenin undergoes phosphorylation, resulting in ubiquitination and consequent proteasomal degradation. On the other hand, in the β-catenin-dependent pathway, after the binding of Wnt ligands to the transmembrane frizzled (Fzd) receptor, the disheveled protein prevents the phosphorylation of β-catenin inducing the translocation into the nucleus where it stimulates the transcription of anti-apoptotic genes including c-Myc and cyclin D1 [ 48 , 49 ]. Lastly, recent studies seem to show that ERKs might be able to increase rather than decrease the levels of anabolic biomarkers in degenerative human chondrocyte [ 50 , 51 , 52 ].…”
Section: Osteoarthritis Molecular Pathwaysmentioning
confidence: 99%
“…Glucosamine (GlcN) is an amino monosaccharide component of glycosaminoglycan (GAG) chains, usually in the form of sulfate or hydrochloride salts derived from the chitin of the exoskeleton of crustaceans and from mushrooms [ 26 ]. Glucosamine promotes the proliferation of human osteoblasts modulating the mTOR pathway and enhancing β-catenin nuclear translocation with consequent activation of cell proliferation via cyclin D1 expression [ 49 , 121 , 137 ].…”
Section: Nutrigenomic: Role Of Nutraceuticals On Osteoarthritismentioning
confidence: 99%